ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE DENGAN PROFIL PERUSAHAAN SEBAGAI VARIABEL MODERASI - Fitriah Ayu Sugianti, (2021)
This study aims to analyze the effect of tax aggressiveness and media exposure on CSR disclosures with company size and leverage as control variables and company profile as a moderating variable in manufacturing companies in the consumer goods industry sector from 2015 to 2019. This study is a quantitative study with purposive sampling method. and found 155 observations. The test uses panel data with the Eviews 10 Program with a Random Effect Model approach. The results of the study show that tax aggressiveness has a positive effect on CSR disclosure and media exposure has no effect on CSR disclosure. The company profile does not moderate the relationship between tax aggressiveness and CSR disclosure, but the company profile moderates the relationship between media exposure and CSR disclosure.